Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.1387/ijdb.113442jm
|View full text |Cite
|
Sign up to set email alerts
|

Planarian embryology in the era of comparative developmental biology

Abstract: During the last decade, the field of evolutionary developmental biology (evo-devo) has emerged as a major research discipline in modern biology and an essential approach to understanding evolutionary relationships in the animal kingdom. At the same time, planarians have become a useful and important model with which to address basic questions regarding the molecular and cellular basis of regeneration, tissue repair and stem cells in adult organisms. Nevertheless, little attention has been paid to their embryon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 32 publications
(34 reference statements)
0
29
0
Order By: Relevance
“…A yolk gland is a reproductive organ filled with planarian nurse cells, namely yolk gland cells. Planarian eggs are called composite eggs (cocoons), which have several fertilized eggs and numerous yolk gland cells444546. Levels of a yolk gland marker gene, Dryg 47, were extremely high in fresh cocoons collected within a day of deposition (see Supplementary Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A yolk gland is a reproductive organ filled with planarian nurse cells, namely yolk gland cells. Planarian eggs are called composite eggs (cocoons), which have several fertilized eggs and numerous yolk gland cells444546. Levels of a yolk gland marker gene, Dryg 47, were extremely high in fresh cocoons collected within a day of deposition (see Supplementary Fig.…”
Section: Discussionmentioning
confidence: 99%
“…This is one of the reasons the sexual worms contained much larger quantities of ᴅ- Trp than the asexual worms. Substances contained in yolk gland cells are used as nutrients for embryogenesis444546. Thus, the embryos may receive ᴅ- Trp.…”
Section: Discussionmentioning
confidence: 99%
“…The German term "Blastomerenanarchie," which was initially used to describe the early embryology of planarians, could also be applied to salp embryology (Martín-Durán et al 2012).…”
Section: Thaliacean Embryology: From Oviparity To Viviparitymentioning
confidence: 99%
“…The majority of species analysed with respect to their potential to regenerate are freshwater animals (Brøndsted 1969 ), but embryological studies have been reported from representatives of all three habitat types. Whereas the freshwater planarian Schmidtea mediterranea has emerged as the model for the study of regeneration mechanisms and stem-cell biology, its sister species Schmidtea polychroa has become the model of choice for embryological studies (reviewed in Martín-Durán et al 2012a ).…”
Section: Tricladidamentioning
confidence: 99%
“…Blastomeres that form the primary epidermis, the embryonic pharynx, or remain undifferentiated in the syncytium each have a specifi c molecular profi le. Thus, the expression of βcatenin -1 , a master regulatory gene for the formation of the endomesoderm across metazoans, is restricted to the cells that form the embryonic pharynx, and these cells express genes related to specifi cation of the mesoderm ( twist and myosin heavy chain ) and endoderm ( foxA ) (Martín-Durán et al 2010, 2012a. This segregation of different groups of blastomeres is also directly related to the establishment of the primary embryonic organization, which represents the scaffold along which the defi nitive embryo will develop.…”
Section: Gastrulation In Neoophoran Platyhelminthesmentioning
confidence: 99%